Achieving exceptional creep resistance in rare-earth-free Mg-base alloys by engineering the shape, size and fraction of eutectic, particles and precipitates. (15th March 2019) - Koundinya, N.T.B.N.; Kottada, Ravi Sankar
Abstract: Creep characterization of five rare-earth-free Mg-base alloys having distinct variations in microstructural features is investigated. Mg-base alloys exhibiting double minimum creep is observed for the first time. Lamellar eutectic microconstituent is responsible for this unique creep behaviour. Dislocation substructures at minimum creep rate observed to be similar in all the five alloys. Majority of the dislocations are of 〈 a 〉 type lying on basal plane. Presence of fine precipitates of Mg2 Ca and particles of CaMgSn along with thick lamellar eutectic enhanced the load-bearing capacity resulting in higher creep resistance. Thick lamellar eutectic decreases the damage nucleation by arresting the cracks. Graphical abstract: Unlabelled Image